On simple scheme of finite/fixed-time control design. Issue 6 (2nd June 2020) - Zimenko, Konstantin; Polyakov, Andrey; Efimov, Denis; Perruquetti, Wilfrid
ABSTRACT: Control laws are designed for stabilisation of a chain of integrators of arbitrary degree in finite and fixed time. Presented control laws are obtained with use of Lyapunov function method and homogeneity concept. The present analysis is based on use of explicitly defined Lyapunov function that is the hallmark with respect to similar works. This analysis allows to get simple procedure of parameters tuning and obtain new estimates for settling-time function. The theoretical results are supported by numerical examples.